Inhabiting the Outside. The opening to the non-human in the techno-artistic experimentations - Cuomo, Vincenzo (Scenari, 2021)
The essay reflects on some lines of contemporary techno-artistic research (in particular on immersive and hybridizing poetics), in the light of the philosophical paradigm of object oriented ontology, and shows how it was anticipated by the theoretical and experimental work of John Cage in the 1950s. – Sixty of the last century. Assuming this theoretical perspective, the question of how we became “post-human” is necessarily transformed into another: how do we think of our non-human being?